Blocking soluble Fas Ligand ameliorates pemphigus: PC111 efficacy in ex-vivo human pemphigus models - Lotti, Roberta; Hundt, Jennifer E.; Ludwig, Ralf J.; Hammers, Christoph M.; Bennett, Brydon; Amato, Antonino; Marconi, Alessandra; Pincelli, Carlo (Frontiers in Immunology, 2023)
Pemphigus is a life-threatening, chronic, autoimmune bullous disease affecting both the skin and the mucous membranes. Based on the mainstream concept that blister formation occurs upon binding of autoantibodies to their antigen proteins (desmoglein1, DSG1 and desmoglein3, DSG3), current therapies mostly aim to suppress the immune system. To avoid the severe side effects associated with the chronic use of immunosuppressive treatments, we have developed PC111, a human monoclonal antibody targeting human Fas ligand (FasL). We have provided a number of in vitro and in vivo evidences showing that soluble FasL induces keratinocyte apoptosis followed by acantholysis. An anti-murine FasL prevents blister formation in the pemphigus neonatal mouse model. To confirm the mechanism of action (MoA) and the efficacy of PC111 in a human pemphigus context, we used the keratinocyte dissociation assay and two independent Human Skin Organ Cultures (HSOC) pemphigus models. PC111 reduced acantholysis in vitro, as shown by the dose-dependent reduction of fragments in the monolayer cultures. In the first HSOC model, normal human skin was subcutaneously injected with a scFv antibody-fragment directed against DSG1 and DSG3, resulting in a severe acantholysis (70-100%) after 24 hours. PC111 inhibited blister formation to around 50% of control. In the second model, normal human skin was injected with a mixture of pemphigus patients’ autoantibodies resulting in a less severe acantholysis (20-30%). PC111 significantly suppressed blister formation to more than 75% up to 72 hours. These results confirm PC111 MoA and demonstrates the efficacy of the anti-FasL antibody also in a pemphigus setting.